Embryo quality, and not chromosome nondiploidy, affects mitochondrial DNA content in mouse blastocysts. Issue 7 (27th November 2018) - Jing, Ying; Li, Li; Li, Yuan‐Yuan; Ouyang, Ying‐Chun; Sun, Qing‐Yuan; Zhang, Cui‐Lian; Li, Rong
Abstract: It has been shown recently that there is premature mitochondria biosynthesis in blastocysts from older women whose egg or embryo quality is poor and that aneuploid blastocysts also have a high number of mitochondrial DNA (mtDNA) copies. Whether nondiploidy/aneuploidy or reduced egg or embryo quality causes premature mitochondrial biosynthesis is not known. This study constructed haploid, diploid, triploid, and tetraploid blastocysts by parthenogenetic activation, intracytoplasmic sperm injection with one or two sperm heads, blastomere electrofusion, respectively, and generated reduced cytoplasm quality embryos from diabetic mouse and in vitro fertilization of aged oocytes, and examined whether nondiploidy or reduced cytoplasm quality causes premature mitochondrial biosynthesis. MtDNA numbers of each blastocyst from different models were tested by absolute quantitative real‐time polymerase chain reaction. It was found that mtDNA content in preimplantation embryos was not associated with their chromosome ploidy, while mtDNA copy numbers in embryos with suboptimal quality were increased. Therefore, it might be the reduced cytoplasmic quality, and not chromosome nondiploidy, that causes premature mitochondria biosynthesis in blastocysts. Abstract : Mitochondria prematurely replicate in blastocysts from aged women and in nondiploidy blastocysts, which have decreased developmental potential. Here, we show that the cytoplasmic quality, and not chromosome ploidy, causes premature mitochondrial biogenesis in early embryo development.